THE EFFECT OF TASK BASED LEARNING METHOD USING ANCHOR PODCAST APPLICATION ON STUDENTS’ SPEAKING ABILITY - Holil Amsori; Muhammad Anjar Nugraha; Jufrianto Sibarani (STKIP Siliwangi, 2023)
This research was conducted with the aim of identifying: (1) the effect of the task-based learning method Task-Based Learning (TBL) seems appropriate to be implemented during Covid 19 pandemic. Anchor podcast is one of the applications might be support to be used in this Internet of things (IoT) era. This research was conducted with the aim of identifying: (1) the effect of task-based learning method (anchor podcast application) on students' speaking ability; (2) the difference in the improvement of results between students who use the TBL-Anchor podcast and students who use the Discussion Method; (3) the students’ responses after using task-based learning methods using anchor podcast application. This quasi-experimental research took the data from test, observations and questionnaires. The experimental class was given three meetings treatment by the anchor podcast application media. Meanwhile the control was given in the students’ discussion method. There are three main findings in this research. First, the significance value of 0.000 is smaller than <0.05, it can be concluded that H0 is rejected and Ha is accepted. Second, the paired sample ttest, of the experimental class score is 14.666, it is higher than the control class which is 7.823. Third, the most perception aspect that the students got is affective aspect rather than cognitive, and behavior.